2021
DOI: 10.1177/0267658321997900
|View full text |Cite
|
Sign up to set email alerts
|

Sentence comprehension in heritage language: Isomorphism, word order, and language transfer

Abstract: This study examines the role of cross-linguistic transfer versus general processing strategy in two groups of heritage speakers ( n = 28 per group) with the same heritage language – Russian – and typologically different dominant languages: English and Estonian. A group of homeland Russian speakers ( n = 36) is tested to provide baseline comparison. Within the framework of the Competition model (MacWhinney, 2012), cross-linguistic transfer is defined as reliance on the processing cue prevalent in the heritage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…It is well known that older adults demonstrate more difficulties in processing syntactically non-canonical sentences compared to canonical sentences ( Sung, 2015 ; Sung et al, 2017 ). Furthermore, research has reported the benefits of isomorphic mapping sentences over non-isomorphic mapping in sentence comprehension among PWA ( O’Grady and Lee, 2005 ), second language speakers ( Chrabaszcz et al, 2022 ; Shin and Park, 2023 ). In our study, we explored a unique case where a mismatch exists between NOM-first (syntactically canonical but non-isomorphic) and COMP-first (non-canonical but isomorphic) sentences.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that older adults demonstrate more difficulties in processing syntactically non-canonical sentences compared to canonical sentences ( Sung, 2015 ; Sung et al, 2017 ). Furthermore, research has reported the benefits of isomorphic mapping sentences over non-isomorphic mapping in sentence comprehension among PWA ( O’Grady and Lee, 2005 ), second language speakers ( Chrabaszcz et al, 2022 ; Shin and Park, 2023 ). In our study, we explored a unique case where a mismatch exists between NOM-first (syntactically canonical but non-isomorphic) and COMP-first (non-canonical but isomorphic) sentences.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed explore how heritage speakers with two different dominant languages processed Russian cases. Participants listened to Russian sentences with a locative or instrumental case and selected an image that best represented the auditory stimulus (Chrabaszcz et al, 2022). They found that English-dominant, but not Estonian-dominant, speakers used word-order cues and misread Russian thematic cues in the locative and instrumental cases (Chrabaszcz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Participants listened to Russian sentences with a locative or instrumental case and selected an image that best represented the auditory stimulus (Chrabaszcz et al, 2022). They found that English-dominant, but not Estonian-dominant, speakers used word-order cues and misread Russian thematic cues in the locative and instrumental cases (Chrabaszcz et al, 2022). Estonian-dominant participants had native-like comprehension of the cases but slower task RTs (Chrabaszcz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations